Virtual reality: a promising instrument to promote sail education - Ji, Fa; Zhang, Xingjian; Zhao, Shan; Fang, Qun (Frontiers in Psychology, 2023)
Sailing has gained an increasing attention among children and adolescents in China, which raised a strong need for sail courses through physical education (PE). However, challenges in teaching practice arise with rapid development of the sport. In the current study, we proposed a perspective that virtual reality (VR) technology makes high-quality sail education accessible for students. Critical analysis summarized the prominent features that enhance sail education, including immersive experience, interactive learning, the first-person view, and practice under well-controlled conditions. Further, research on VR sport training indicated successful transfer from virtual environment to real situation. Specifically, significant improvement in skill performance and tactical behaviors were identified, which was attributed to the enhanced perception-action coupling after VR training. Additionally, VR-based coding programs provide students with affordances of designing the virtual environment. The content design education promotes comprehension and application of knowledge and theories when students develop the simulated environment with a high level of presence. Therefore, VR technology is a promising instrument to meet the increasing demand on sail education. While VR enriches educational resources for a large class size, the interdisciplinary feature of VR-based sail course can attract students with different study interests and backgrounds to the class.